Perancangan Sistem E-Parking Berbasis Arduino dengan Kartu RFID - Muhammad Ferdi Herdiansyah; Muhtajuddin Danny; Retno Fitri Astuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Security and efficiency of parking management are crucial aspects in the operations of companies and educational institutions. At Pelita Bangsa University, the conventional parking system still uses manual methods and paper-based tickets, which is inefficient and potentially creates security issues. In addition, the lack of integration between the parking system and vehicle identification increases the risk of theft. This research aims to design an RFID-based parking system that can be accessed using a Student Identity Card. The system uses RFID at low frequencies to ensure the security and accuracy of vehicle identification. The results show that the RFID system is able to efficiently replace conventional methods, reduce paper usage, and increase parking access speed. The system is also integrated with the student database, enabling better access control and automatic recording of vehicles. The implementation of the system in Pelita Bangsa University's parking area not only improves security but also user experience, with a faster payment process and structured vehicle data management. Hopefully, this system can be an innovative solution that can be applied in various institutions to face the challenges of parking security and efficiency in the digital age.